The effect of thermal processing in oil on the macromolecular integrity and acrylamide formation from starch of three potato cultivars organically fertilized - Varzakas, Theo; Alghamdi, Asma; Alghamdi, Hanan; Linforth, Rob S.T.; Dinu, Vlad; Besong, Tabot D.; Gillis, Richard B.; Adams, Gary G.; Arapoglou, D.; Connerton, Ian F.; Harding, Stephen E.; Israilides, C. (Taylor & Francis Online, 2016)
Starches from three organically produced cultivars of potato tuber (Lady Rosetta, Spunta and Voyager) have been studied in relation to (i) acrylamide production (ii) macromolecular integrity after frying with extra virgin olive oil, soybean oil and corn oil. During cultivation, a treatment involving the combination of nitrogen, phosphorus and potassium fertilization under organic farming was applied (N1, P2, K1 where Ν1 = 1.3 g Ν per plant, P2 = 5.2 g P2O5 per plant, Κ1 = 4.0 g K2O per plant).